2004
DOI: 10.1093/petrology/egh083
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and Origin of Andalusite in Peraluminous Felsic Igneous Rocks

Abstract: Andalusite occurs as an accessory mineral in many types of per aluminous felsic igneous rocks, including rhyolites, aplites, granites, pegmatites, and anatectic migmatites. Some published stability cunes for And = Sil and the water-saturated granite solidus permit a small stability field for andalusite in equilibrium with, felsic melts. We examine 108 samples of andalusite-bearing felsic rocks from more than 40 localities worldwide. Our purpose is to determine the origin of andalusite, including the T-P-X cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
51
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 90 publications
(57 citation statements)
references
References 90 publications
(102 reference statements)
5
51
0
1
Order By: Relevance
“…3a for illustrative purposes. The compositions are very similar to those reported for other andalusites crystallized from a magma (D'Arnico et al 198 1;Gordillo et al 1985;Kawakami 2002;Clarke et al 2005), i.e. Al 2 0 3 between 62.90 and 64.26 wt%, and small amounts of Fe203 (0.42-0.51 wt%).…”
Section: Anaiyticai Methodssupporting
confidence: 87%
See 4 more Smart Citations
“…3a for illustrative purposes. The compositions are very similar to those reported for other andalusites crystallized from a magma (D'Arnico et al 198 1;Gordillo et al 1985;Kawakami 2002;Clarke et al 2005), i.e. Al 2 0 3 between 62.90 and 64.26 wt%, and small amounts of Fe203 (0.42-0.51 wt%).…”
Section: Anaiyticai Methodssupporting
confidence: 87%
“…The high ASI values (1.27-1.42; Table 2) of the Santa Cruz igneous facies suggest that the granitic magma was saturated in alurnina, making Gordillo et al 1985 ;Clarke 1995 ;Dahlquist et al 2005;Clarke et al 2005 and references therein). In addition, Patiño Douce (1992) has shown that the activity coefficient of Al in silicic melts is a function of the alkali content of the melt, whereby alkali-rich a Mg Na Fig.…”
Section: Whole-rock Chemistrymentioning
confidence: 99%
See 3 more Smart Citations